Ionic Liquid Promoted Synthesis of Conjugated Carbon Nitride Photocatalysts from Urea. Issue 6 (1st April 2014) - Lin, Zhenzhen; Wang, Xinchen
Abstract To allow for simultaneous textural engineering and doping of carbon nitride materials with heteroatoms, urea has been polymerized with an ionic liquid. The role of urea is to create a delamination effect during carbon nitride synthesis, whereas ionic liquid functions as texture modifier as well as B/F dopant source. This will result in the rational fabrication of boron‐ and fluorine‐containing 2D carbon nitride nanosheets with enhanced optical harvesting and charge separation capabilities for hydrogen evolution catalysis using visible light. We believe that the innovative modification strategy developed herein can be coupled with the already known modification tools of 2D carbon nitride, thus further developing a new family of light‐harvesting 2D platforms for the efficient and sustained utilization of solar radiation for a variety of advanced applications, including CO2 photofixation, organic photosynthesis, and pollutant controls.